DFT and molecular docking analyses of the effects of solvent polarity and temperature on the structural, electronic, and thermodynamic properties of p-coumaric acid: Insights for anti-cancer applications - Umer Sherefedin; Abebe Belay; Kusse Gudishe; Alemu Kebede; Alemayehu Getahun Kumela; Tadesse Lemma Wakjira; Dereje Gelanu; Tesfaye Feyise; Jebel Haji Mahamud; Abdulkerim Abdela; Kebede Shankute Gizew (Results in Physics)
This study investigated the effects of solvent polarity and temperature on the structural, electronic, and thermodynamic properties of p-coumaric acid (p-CA) and its interaction with caffeine, a promising natural phenolic compound for cancer treatment because of its ability to inhibit tumor growth and induce apoptosis. This work investigated the impact of these factors via computational techniques, including semiempirical methods (MP6), Hartree–Fock (HF) calculations with the 6-311＋＋G (d, p) basis set, and density functional theory (DFT) with various basis sets, such as STO-3G*, SDD, 3-21＋G*, Aug-CC-pVDZ, 6-31＋＋G (d, p), LANL2DZ, 6-31＋＋G’ (d, p), and 6-311＋＋G (d, p). DFT calculations revealed notable changes in the geometric features of p-CA, including bond angles, dihedral angles, and bond lengths, in both vacuum and water. Furthermore, the results indicated that solvent polarity caused variations in the Fourier transform infrared (FTIR) spectra, absolute and solvation energies, dipole moment, and HOMO–LUMO gap. The thermal analysis also revealed that increasing the temperature from 100 K to 1000 K led to higher enthalpy, heat capacity, and entropy, along with a decrease in Gibbs free energy values due to enhanced molecular vibrations, contributing to the degradation and instability of p-CA. Time-dependent DFT (TDDFT) analysis revealed that solvent polarity influenced UV–Vis absorption and excited-state dipole moments, leading to significant changes in electronic transitions. Additionally, molecular docking studies indicated that p-CA achieved strong binding affinities with various proteins, notably a maximum of −7.5 eV with the 3rts protein; however, the presence of caffeine reduced this binding affinity, suggesting competitive interactions that could diminish its therapeutic effectiveness. These findings underscore the potential of p-CA as an effective anticancer agent, emphasizing the critical roles of solvent, temperature, and molecular interactions in its efficacy.